A cross-sectional study on cardiac autonomic functions and inflammatory markers in chronic fatigue syndrome - Ayasha Nishad; Abhishek Tiwari; Waqas Alauddin; Prajakta Radke (Asian Journal of Medical Sciences, 2024)
Background: Chronic fatigue syndrome (CFS) is a complex multisystem disease that affects around 1 million of the Indian population every year and is characterized by persistent fatigue. CFS is related to cardiovascular illness, and cardiovascular autonomic nervous system dysfunction is often seen. We investigated the state of cardiac autonomic function in CFS and associated it with their level of inflammatory markers and disease severity since there is not much research on the subject. Aims and Objectives: The objective of this study is to evaluate cardiac autonomic functions by using heart rate variability (HRV) in patients with CFS and in healthy controls. The study aimed to evaluate the correlation between HRV and inflammatory markers in patients with CFS and in healthy controls. Materials and Methods: Thirty controls and 30 diagnosed cases of CFS were used in the research. The short-term variability of heart rate was used to measure autonomic function. We measured tumor necrosis factor-alpha (TNF-α) and interleukin (IL-10) in 3 mL of overnight fasting serum. TNF-α and IL-10 were used to evaluate the severity of CFS. Results: Patients with CFS showed a substantial reduction in low frequency (LF) (P=0.00*), high frequency (HF) (P=0.00*), LF/HF ratio (P=0.00*), and time domain parameters of HRV, namely RMSSD (P=0.03*), SDNN (P=0.00*), NN50 (P=0.00*) and total power (P=0.00*). Patients with CFS had considerably higher levels of TNF-α. TNF-α and LF/HF ratio and RMSSD, NN50, and HF were shown to have a substantially favorable correlation. Conclusions: Our research indicates a substantial correlation between autonomic dysfunction and inflammatory activity, as well as the severity of CFS. Therefore, we suggest that HRV might be a useful technique for accurately screening CFS patients for autonomic disruption symptoms early on, which can significantly lower morbidity and death in the future.